Size segregated of atmospheric sulphate aerosols in Johor Bahru - Mohd. Yusof, Mohd. Rashid; Lim, S. F.; A., Rahmalan (1997)
The measurement of atmospheric aerosols samples segregated into six sizes using a cascade impactor was performed at the Air Quality Research Station, University of Technology Malaysia, Johor Bahru. The samples were collected from July to November 1996 and analysed for sulphate using ion chromatography. Results showed that the average sulpahte concentration at the site was 5.58(+-)3.41 micro-gram/m3 which is below the concentration observed on other cities of the world such as those in the Europe and Japan (range 6 micro-gram/m3 - 14 micro-gram/m3). The size distribution of sulphate showed a strong concentration peaks at both 1.32 micrometer and 4.5 micrometer which can be attributed to non-sea salt and sea salt sulphate origin respectively. The non-sea salt sulphate which was found to be predominantly in the fine size fraction is an anthropogenic related pollutant. While the sea salt sulphate aerosol was found to be transported from the nearest marine environment (i.e from the S-SE wind sector). Evidently, sea salt sulphate aerosol concentration was consistently showed a positive correlation with wind speed term throughout the study.